Comprehensive transcriptome and metabolome analysis to exploration the effects of TCs on GCs lipid metabolism at goose pre-ovulatory follicle - Jisi Ma; Wenqiang Sun; Xin Yuan; Hongyu Long; Hui Shen; Chunying Liu; Xiang Gan (PLoS ONE, 2026)
Granulosa cells (GCs) and theca cells (TCs) have complex communication and interactions. Lipid metabolism in GCs is important for follicle development, which is also inseparable from the role of TCs; however, the underlying mechanisms remain unclear. In this study, we selected the pre-ovulatory (F1) follicle of geese—a poultry species with relatively low egg production—which exhibits high lipid content and vigorous lipid metabolism. Using transcriptomic and metabolomic approaches, we analyzed the effects of TCs on GCs in a co-culture model. We identified and screened the core functions and signaling pathways associated with the differentially expressed metabolites (DEMs) and genes (DEGs) between the mono-culture and co-culture groups. Key metabolites and genes within the core pathway were subsequently validated using ELISA and qPCR. Both transcriptomic and metabolomic results showed that after co-culture, the metabolite and gene expression profiles of GCs were significantly altered. Enrichment analysis revealed that both DEMs and DEGs were significantly associated with sphingolipid and glycerophospholipid metabolism pathways. In the co-culture group, metabolomic and ELISA results indicated that the concentrations of core metabolites, phosphorylcholine (PC) and phosphatidylethanolamine (PE), in GCs increased significantly ( p < 0.05). Transcriptomic and qPCR results both showed that the expression levels of genes involved in PC catabolism, including phospholipase A2 epsilon-like-1, cytosolic phospholipase A2 epsilon-like-2, and phospholipase A2-like genes in GCs decreased significantly ( p < 0.05). In summary, our results suggest that TCs may affect the lipid metabolism of GCs in goose F1 follicles by promoting PC synthesis within the glycerophospholipid metabolism pathway.